Texture: Faking the physical. Issue 1 (1st August 2019) - Stevenson, Gabrielle Brace; Stevenson, Nicholas
Contemporary illustration is infatuated with texture. The imperfections of analogue processes and signs of physical decay, which were once incidental, or even irritating, are now highly sought after and frequently replicated in order to provide an ornamental layer to contemporary digital illustration. Nicholas Stevenson is an illustrator who uses texture this way. His visual language centres around analogue textures that are digitally applied from an ever-growing library of scanned surfaces: taken from worn book jackets, watermarked paper and ink smudges. This visual essay explores this topic through Nicholas's illustrations in dialogue with Gabrielle's written, critical commentary. Drawing on Mark Fisher's ideas about hauntology in twenty-first-century western culture, and Jean Baudrillard's simulacra, we intend to explore the latent effects of the ornamental application of analogue texture in digital illustration, with Nicholas Stevenson's work taking the role of both example and co-contributor.